2011
DOI: 10.1039/c1dt10071h
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting behavior of type-I Si clathrate K8Ga8Si38

Abstract: A ternary type-I Si clathrate K(8)Ga(8)Si(38) has been revealed to be an indirect band gap semiconducting material with an energy gap (E(g)) of approximately 0.10 eV, which is much smaller than the calculated E(g) value that is 0.15 eV wider than E(g) of elemental Si with the diamond-type structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 30 publications
8
62
0
Order By: Relevance
“…We recently synthesized K 8 Ga 8 Si 38 and confirmed that this is a semiconductor, though estimated band gap value, E g , from resistivity and optical absorption is much narrower than the value of theoretical prediction [6].…”
Section: Introductionmentioning
confidence: 82%
“…We recently synthesized K 8 Ga 8 Si 38 and confirmed that this is a semiconductor, though estimated band gap value, E g , from resistivity and optical absorption is much narrower than the value of theoretical prediction [6].…”
Section: Introductionmentioning
confidence: 82%
“…This should be the reason the substitutional formation energy is the smallest at 6c site and largest at the 16i site. In addition, 41) and occupancy of Ga at the 6c, 16i and 24k sites were 0.607, 0.026 and 0.179, respectively, 42) which is nearly equivalent to (6c, 16i, 24k) = (4, 0, 4). However, the present calculation is consistent with these experimental results in that Ga is difficult to substitute at the 16i site.…”
Section: Codoping Of Guest and Substitutional Atommentioning
confidence: 93%
“…41) They suggested that the discrepancy between the observed band gap and their calculated one (0.798 eV 15) ) may be due to random substitutional positioning of Ga, vacancies, nonstoichiometry, and so on. It can be considered that random Ga configuration does not significantly narrow the band gap because the change in the band gap was found to be at most 0.1 eV, as demonstrated by changing the Ga configuration in the present work.…”
Section: Implication For Recent Experimental Investigationmentioning
confidence: 99%
“…Therefore, it is necessary to find ternary Si clathrates with superior ZT values. (E g ) that range from 0.20 eV below to 0.24 eV above the E g value for elemental Si with the diamond-type structure [19,20]. Elemental Si has an E g of 1.1 eV; therefore, the E g values of these clathrates range from 0.90 to 1.34 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, K 8 Ga 8 Si 38 was experimentally revealed to be a semiconductor [19] with an E g of 1.2 eV [22]. As the next step, we attempted to replace Ga with Al in consideration of the sustainability of raw material supplies and toxicity issues.…”
Section: Introductionmentioning
confidence: 99%